The Best Medicine? Psychotherapists’ Experience Of The Impact Of Humour On The Process Of Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
Although afforded very little, if any, attention in formal psychotherapy training and literature, humour is a ubiquitous and central existential expression; a powerful and fundamental relational phenomenon significant to the practice of psychotherapy. We report a qualitative study on the use of humour in therapy. The findings confirm the double-edged nature of humour that emerged in our study of the humour literature (Gibson & Tantam, 2017). Used judiciously in practice, humour can reveal and help develop an existential maturity, a tragi-comic attitude in which a creative acceptance of limitations and paradox is possible. But if the timing is off, or the therapist uses humour defensively, it can inhibit the psychotherapeutic process.
Keywords: Humour; ambiguity; tragi-comic; paradox; catalyst; power; process